Optimalisasi Model Pembelajaran Berbasis Proyek (Project Based Learning) untuk Meningkatkan Keterampilan Menulis Karya Ilmiah - Pontjowulan Pontjowulan (CV. Syntax Corporation Indonesia, 2023)
This study aims to determine the increase in students' writing skills through project-based learning (Project Based Learning). The subjects of this study were students of class XI BDP-2 at SMK Negeri 9 Samarinda for the 2021/2022 academic year, a total of 33 students. Writing a class action research report (CAR) uses a descriptive method. Collection of information to determine students' writing ability by using tests. The technique used is face-to-face learning in class through several stages, namely: (1) the teacher prepares the Lesson Plan (RPP), (2) the teacher prepares learning materials and assignments, (3) students study the material, (4) the teacher monitors activities teaching and learning in class, (5) the teacher provides feedback on learning and assignments that have been done by students. The use of project-based learning models (Project Based Learning) can improve students' ability to write scientific work texts. The average value of student learning outcomes after using the project-based learning model (Project Based Learning) is 69.70%, an increase of 30.31% compared to the mastery learning before using the project-based learning model (Project Based Learning) which reached 39.39%. on scientific work text material.